PERBANDINGAN PENGATURAN MEREK DAN INDIKASI GEOGRAFIS BATIK BETAWI DI INDONESIA DAN BATIK KELANTAN DI MALAYSIA - Carmiya, Carmiya; Yunari, Sri Bakti (Tribuere, 2024)
Geographical Indication Protection is growing rapidly, especially in Asia. ASEAN countries are active in identifying and registering Geographical Indications to increase the presence of national and international markets. One of the developments in the protection of Geographical Indications is Betawi Batik and Kelantan Batik. The main issue is regarding the similarities and differences in the regulation of the geographical indication of Betawi batik in Indonesia and Kelantan batik in Malaysia. And legal protection for the geographical indication of Betawi batik in Indonesia and Kelantan batik in Malaysia. This thesis uses a normative type with a comparative legal research method. The research data uses secondary data and primary data, drawing conclusions using a deductive method by analyzing qualitatively. This thesis can be concluded regarding the similarities in the regulation of IG Betawi batik and Kelantan batik referring to the legal rules of Geographical Indications in Indonesia and Malaysia by implementing a mandatory IG registration system by identifying goods/products originating from their respective geographical areas. While the differences in IG Betawi batik in Indonesia are regulated by Law No. 20/2016 MIG. Kelantan Batik in Malaysia is regulated by the Geographical Indications Act 2022. The registration process for Geographical Indications in Indonesia is through DJKI, while IG in Malaysia is through MyIPO. In law enforcement in Indonesia, if a violation occurs, it can be through the courts, in Malaysia through a special institution and/or by imposing administrative sanctions. The requirements for obtaining IG legal protection are by submitting an application to the government. The term of protection for Geographical Indications for Betawi batik in Indonesia is as long as the reputation, quality, and characteristics are maintained, while the IG for Kelantan batik in Malaysia is for 10 years and can be extended.